Strategi UMKM di Alun – Alun Kidul Yogyakarta untuk Meningkatkan Kualitas Layanan dan Produk Penjualan - Mutiara Agus Wahyuni; Hurian Kamela (Jurnal Riset Ekonomi dan Akuntansi, 2025)
The aim of this research is to analyze MSME strategies related to customer satisfaction with quality services and products. This study applies a quantitative approach. Fifty respondents from the MSME consumer population who buy food and drinks in the southern Alun - Alun area were involved in this research. The results show that better product service can increase customer satisfaction.